Business model with the application of social networks in rural Msmes of the Chone Canton, the year 2022 - Avila-Rosales, Francisca Margarita; Zambrano-Alcivar, Katty Gisella; Mendoza-Garcia, Karen Alejandra; Mendoza-Cedeño, Henry Fabricio (International research journal of management, IT and social sciences, 2023)
The objective of the research was to implement a business model, using social networks as a tool for the development of the Virgen de Guadalupe spa, whose problem focuses on developing a business model applying social networks in the Virgen de Guadalupe spa. The study refers to the fact that today business models in social networks are focused on making users spend as much time as possible on the screen, which is why one of the ideas raised in the research is to establish multiple tools that allow development, through the application of digital marketing within the spa. The applied methodology has a qualitative approach, being of a field type due to its variables, documentary and bibliographical consultation for its understanding and justification, the methods used are inductive-deductive and analytical. The results can be evidenced through the market study of the "La Virgen de Guadalupe" spa, where an analysis was carried out through internal and external methods, the five forces of Porter, the tourist attraction, weaknesses, and strengths.